2016
DOI: 10.1007/s13139-016-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Imaging of Pulmonary Mucinous Cystadenocarcinoma with Signet Ring Cells

Abstract: A 63-year-old male with a recently diagnosed right lung lesion was referred for staging. F-FDG PET/CT scan revealed a hypodense, cystic-like mass in the right upper lung lobe, which demonstrated low, diffuse F-FDG uptake, likely due to the presence of mucus, as well as intensely hypermetabolic right hilar and right paratracheal lymph nodes. Transbronchial biopsy revealed a primary pulmonary mucinous cystadenocarcinoma with the presence of signet ring cell carcinoma, a co-existence of two rare variants of lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Because a diagnosis of PMCN is difficult to establish, some authors tried using positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose integrated with computed tomography (PET-CT 18F-FDG). This revealed low and diffuse capture in the pulmonary lesion, but much more intense in the hilar and paratracheal lymph nodes, especially in cystadenocarcinomas (29). In other cases, capture was intense in the solid portion of the lesion wall and significantly lower in the cystic part (26).…”
Section: Discussionmentioning
confidence: 94%
“…Because a diagnosis of PMCN is difficult to establish, some authors tried using positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose integrated with computed tomography (PET-CT 18F-FDG). This revealed low and diffuse capture in the pulmonary lesion, but much more intense in the hilar and paratracheal lymph nodes, especially in cystadenocarcinomas (29). In other cases, capture was intense in the solid portion of the lesion wall and significantly lower in the cystic part (26).…”
Section: Discussionmentioning
confidence: 94%
“…3 At times, it may not be possible to locate the SRCC because of low fluorodeoxyglucose uptake on PET scan, probably due to the high quantity of mucin. 4 In general, CM heralds a poor prognosis, with the average survival time being < 1 year. When the primary is SRCC, the clinical course is more aggressive irrespective of the site, and shows poor response to chemotherapy.…”
Section: Dear Editormentioning
confidence: 99%
“…Signet‐ring cell carcinoma (SRCC) of the lungs, a variant of poorly differentiated adenocarcinoma, is frequently found in young, nonsmoking patients 3 . At times, it may not be possible to locate the SRCC because of low fluorodeoxyglucose uptake on PET scan, probably due to the high quantity of mucin 4 . In general, CM heralds a poor prognosis, with the average survival time being < 1 year.…”
Section: Figurementioning
confidence: 99%
“…Such an approach is an exploitation of the functional asymmetry between neoplastic cells and healthy neighboring cells with a therapeutic aim. Evidence of such functional asymmetry is readily apparent in positron emission tomography studies (PET-CT), and references to cancer hypermetabolic phenotype are also abundant in the literature [3][4][5][6]. Robust in vitro studies have shown the respiratory quotient (RQ=CO2/O2) of ascites cells and isolated neoplastic cells to be invariably depressed even in the presence of sufficient paO2 in the culture medium, i.e.…”
Section: Preliminary Considerationsmentioning
confidence: 99%